Cost Effectiveness and Quality Adequacy in Construction Project - Koirala, Madhav Prasad (Journal of Lumbini Engineering College, 2022)
This article looked at the challenges of defining quality in the construction business, the potential benefits of executing quality, and the roadblocks to using quality in development. We use information gathered during contractor interviews as well as information from questionnaire surveys. Clients want better service quality, faster construction, and technological advancements. It's no coincidence that the building industry has turned to manufacturing as a source of inspiration and innovation. Total Quality Management (TQM Generation and Re-engineering) and other fabrication-based methodologies are being encouraged and integrated into the development process. Because of its excellence, it has made more progress than any other benefit industry. However, because of the requirement for standardization and the multiple stakeholders involved, implementing TQM standards in development is particularly difficult.